Constitutional court attitudes and the COVID-19 pandemic—case studies of Hungary, Serbia, and Croatia - Beretka, Katinka; Ősze, Áron (Frontiers in Political Science, 2025)
The paper analyses the practice of the constitutional courts of Hungary, Serbia and Croatia, in terms of the constitutionality and legality of the normative responses to the COVID-19 pandemic in the countries examined. The goal is to critically present the arguments along which the constitutional courts ensured (or attempted to achieve) the balance between the protection of fundamental rights and the preservation of the public interest and public health in their decisions related to the COVID-19 pandemic; and to deduce whether any similarities can be discovered in the reasoning of the courts or they have adopted a completely different approach from each other. According to the results of the legislative research, regional experience of the examined neighbouring countries with similar legal and political traditions, constitutional court structures, and political leadership styles shows that even in circumstances of a global, uniform health crisis, distinct national reactions might be expected. However, on the other side, the case law research gave a completely different conclusion, supporting the highly similar reasoning of the constitutional courts that almost without exception have given priority to public interest in combating the epidemic over fundamental rights.